Pengembangan Cerita Legenda Tiongkok Xing Tian Wu Gan Qi dari Bahasa Mandarin ke dalam Bahasa Indonesia (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2019)
Dalam penelitian ini, peneliti mengembangkan cerita legenda Tiongkok yang berjudul Xing Tian Wu Gan Qi. Tujuan dari penelitian ini, yaitu (1) mengetahui desain perkembangan cerita legenda Tiongkok di Indonesia, (2) mendiskripsikan hasil validasi ahli mengenai buku cerita legenda terjemahan â€œXing Tian Wu Gan Qiâ€ dari bahasa Mandarin ke dalam bahasa Indonesia, serta (3) mendiskripsikan analisis SWOT tentang cerita legenda â€œXing Tian Wu Gan Qiâ€. Penelitian ini menggunakan metode Research and Development (RD) dengan lima tahapan, yaitu (1) potensi dan masalah, (2) pengumpulan data, (3) desain produk, (4) validasi desain, serta (5) revisi desain.Hasil dari analisis SWOT dari buku cerita dongeng menunjukkan bahwa perlu adanya pembaharuan dalam hal terjemahan maupun desain ilustrasi cerita. Hasil validasi ahli media mendapatkan rata-rata 82,1 dengan skor 3 yang berarti media pengembangan layak atau sesuai untuk digunakan. Validasi oleh ahli bahasa mendapat nilai rata-rata keseluruhan 8,5 dengan skor 3 yang berarti media pengembangan layak atau sesuai untuk digunakan. Saran perbaikan diberikan oleh para ahli pada aspek-aspek tertentu. Saran pada aspek fisik media adalah memperbaiki beberapa bagian tulisan yang terganggu dengan warna, melayout ulang posisi penempatan cerita agar mudah terbaca, penambahan halaman tersendiri untuk sebagian isi cerita yang kurang jelas keterbacaannya. Adapun saran perbaikan yang diberikan oleh ahli bahasa yaitu dengan memperhalus beberapa kalimat.Based on this research, researcher was development the legend of Chinese entitled â€œXing Tian Wu Gan Qiâ€. The purpose of this study, namely (1) to know the design of the development of Chinese legend in Indonesia, (2) to describe the results of expert validation regarding the legendary book of "Xing Tian Wu Gan Qi" translations from Chinese into Indonesian, and (3) to describe the SWOT analysis of the story of the legend of "Xing Tian Wu Gan Qi". This study uses the Research and Development (RD) method with five stages, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and (5) design revisions.The results of the SWOT analysis of fairy tale books show stories needs to be renewal in terms of translation and story illustration design. The results of the media expert validation got an average of 82.1 with a score of 3 which means that the development media is appropriate or suitable to be used. Validation by linguists gets an overall average score of 8.5 with a score of 3 which means that the development media is appropriate or suitable for use. Suggestions for improvement are given by experts on certain aspects. Suggestions on the physical aspects of the media are fixing some parts of the writing that are disturbed by color, rearrange the position of the story placement to make it easy to read, addition of separate pages for some of the contents of the story that is less clear the readability. The suggestions for improvement given by linguists are by refining a few sentences.Â Based on this research, researcher was development the legend of Chinese entitled â€œXing Tian Wu Gan Qiâ€. The purpose of this study, namely (1) to know the design of the development of Chinese legend in Indonesia, (2) to describe the results of expert validation regarding the legendary book of "Xing Tian Wu Gan Qi" translations from Chinese into Indonesian, and (3) to describe the SWOT analysis of the story of the legend of "Xing Tian Wu Gan Qi". This study uses the Research and Development (RD) method with five stages, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and (5) design revisions.The results of the SWOT analysis of fairy tale books show stories needs to be renewal in terms of translation and story illustration design. The results of the media expert validation got an average of 82.1 with a score of 3 which means that the development media is appropriate or suitable to be used. Validation by linguists gets an overall average score of 8.5 with a score of 3 which means that the development media is appropriate or suitable for use. Suggestions for improvement are given by experts on certain aspects. Suggestions on the physical aspects of the media are fixing some parts of the writing that are disturbed by color, rearrange the position of the story placement to make it easy to read, addition of separate pages for some of the contents of the story that is less clear the readability. The suggestions for improvement given by linguists are by refining a few sentences.